Selective Default Expectations - Olivier Accominotti; Thilo N. H. Albers; Kim Oosterlinck (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
This paper explores how selective default expectations affect the pricing of sovereign bonds in a historical laboratory: the German default of the 1930s. We analyze yield differentials between identical government bonds traded across various creditor countries before and after bond market segmentation. We show that, when secondary debt markets are segmented, a large selective default probability can be priced in bond yield spreads. Selective default risk accounted for one third of the yield spread of German external bonds over the risk-free rate during the 1930s. Selective default expectations arose from differences in the creditor countries' economic power over the debtor.
Keywords: F13; F34; G12; G15; H63; N24; N44; 330; sovereign risk; debt default; secondary markets; creditor discrimination